Nombrar lo inexistente: los ‘objetos ausentes’ de Carlos Liscano (Altre Modernità, 2021)
The works of Carlos Liscano, detained in Libertad prison during the military dictatorship in Uruguay (1972-1985), seem to return the vibrant tension of an antagonistic discourse that plays its decisive game against power, the prison institution and the ideologies that structure it. Essential elements of such a process are the ‘absent objects’ that, as passages between one dimension and the other of writing - that of direct testimony and that of greater literary complexity - constitute access points to all of his poetic imagery. In this essay we will analyse the function of these minimal devices - but fundamental in Liscano's writing - especially in Lector Salteado (Vida del cuervo blanco, 2015), text in which it is possible to observe this process of 'memory, resistance and creation', which allows man continues to exist in conditions of deep suffering and deprivation. Simple objects, then, that in common life almost disappear, become, in prison, a metaphor of deep resistance. Their existence through language capable of evoking them, their possibility to be in absentia, determines a constant exercise that allows the detainee the only imaginable way of salvation. Orality and writing that evoke certain absences are imposed as instruments of the mind that cannot accept the lack of real referents and that builds a microcosm of signs, often shared with other prisoners, but also destined to the obsessive discourse of an isolated and fragile individuality: to the secret laboratory of a writer who is being trained, to the complex process of reading, writing, transcribing and rewriting that Liscano carries out.
Keywords: prison; Liscano; objects; Uruguay